Sensitive Bromatometric Methods for the Determination of Sumatriptan Succinate in Pharmaceutical Formulations - K. V. V. Satyanarayana; P. Nageswara Rao (E-Journal of Chemistry)
Two simple and sensitive spectrophotometric methods are described for the determination of sumatriptan succinate (STS) in pure and tablets using bromate-bromide as the bromination reagent in acid medium and two dyes as subsidiary reagents. The two methods are based on the bromination of STS by a known excess of in situ generated bromine followed by determination of unreacted bromine by reacting with a fixed amount of methyl orange (Method A) or indigo carmine (Method B) and measuring the absorbance at 508 or 610 nm. In both methods, the amount of bromine reacted corresponds to the amount of STS. The experimental conditions for the assay have been optimized. In two methods, the absorbance was found to increase linearly with the concentration of STS at the respective wavelengths. Beer’s law was obeyed over the ranges 0.2-1.6 and 2.0-12.0 μg mL-1 for method A and method B respectively and the respective molar absorptivity values were 1.898×105 and 2.71×104 L mol-1 cm-1. The statistical analysis of the methods was validated according to the present ICH guidelines. The proposed methods were applied to the analysis of tablet form of STS and the results tallied well with the label claim.